ANALISIS SENTIMEN ULASAN PENGGUNA APLIKASI GOOGLE PLAY MENGGUNAKAN NAÃVE BAYES - Andriani Nurian (Jurnal Informatika dan Teknik Elektro Terapan, 2023)
In today's digital era, mobile applications are increasingly popular and their use is increasing, so it is important to understand user satisfaction and dissatisfaction in using these applications. One of the most popular mobile applications in Indonesia is the Dana application, which provides various financial services such as bill payments, money transfers, investments, and so on. Sentiment analysis of Dana application reviews on the Google Play Store was carried out using the Naive Bayes algorithm classification method. The purpose of this analysis is to understand user opinions and views on the Dana application, as well as provide input for developers in improving the quality of services and features provided. The results of the analysis show that the majority of users give positive reviews of the Dana application with a percentage of around 60%, while only around 12% have negative reviews, and around 28% have neutral reviews. From the results of this analysis, it can be concluded that the Dana application has received a positive response from users on the Google Play Store. However, there are still a small number of negative reviews which can be input for developers to improve the quality of services and features provided by the Dana application.